Development of peanut-chocolate spread using chocolate syrup - Palang, Pauline Taliase; Galvez, Flor Crisanta F. (2001., 2001)
Six formulations (0%, 10%, 20%, 30%, 40% and 50% chocolate syrup) for a peanut-choco spread were developed by adding different amounts of chocolate syrup to peanut paste. Fifty consumer panelists evaluated the peanut-chocolate spread samples for color, sweetness, chocolate flaa]vor and spreadability using nine-point hedonic scales. A significant difference at 5% level of significance exists for color among all the samples with different levels of chocolate syrup. The control (0% chocolate syrup) and sample with 10% chocolate syrup were significantly different from tne rest of the treatments at 5 % level of significance for chocolate flavor from the samples with different levels of chocolate syrup. There was no significant difference for spreadability among all the samples with different levels of chocolate syrup. the formulation with 20% chocolate syrup received the highest mean scores for color (6.54), sweetness (6.5) and chocolate flavor (6.36) acceptability. The formulation with 30% chocolate syrup had the highest mean scores for spreadability (7.06) and overall acceptability (6.66). results indicated that a peanut-choco spread that is acceptable to consumers may be produced using 30% chocolate syrup in the formulation.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peanuts; Chocolate